Method of drilling process control and experimental studies of resistance forces during bits drilling with PDC cutters - Vyacheslav V. Neskromnykh; Marina S. Popova; A. E. Golovchenko; P. G. PETENEV; Liu Baochang (Записки Горного института, 2020)
A rational, theoretically proved and empirically verified control system is a condition for optimal management of the drilling process in compliance with the criteria for minimizing the cost of time and material resources. A new generation of rock-cutting tools using PDC cutters (polycrystalline diamante cutters), which are extremely effective when drilling wells for various purposes in medium-hard rocks, dictates the need to develop methods and criteria for optimal control of the drilling process using this tool.